1978
DOI: 10.1021/jm00206a022
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin receptor binding affinities of several hallucinogenic phenylalkylamine and N,N-dimethyltryptamine analogs

Abstract: Hallucinogenic phenylalkylamine and N,N-dimethyltryptamine analogues are known to affect serotonergic systems both in vivo and in vitro. Using a rat stomach fundus model, the 5-HT receptor binding affinities of several of these analogues were determined and compared. The most behaviorally potent analogues examined, DOB, DOM, and 5-methoxy-N,N-dimethyltryptamine, were found to possess rather high affirmities (pA2 = 7.35, 7.12, and 7.08, respectively) for the 5-HT receptors of the model system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…N-alkylation or N,N-dialkylation proved detrimental to the potency of most phenylalkylamines. [172,174,175] An exception was found in a series of N-benzyl substituted phenylalkylamines; [176] affinity studies comparing 2C-B (11) with its N-benzylated analogues (29-31) revealed an approximate twofold increase in binding affinity for [ 125 I]DOI labeled 5-HT 2A receptors. Moreover compounds 29-31 showed increased subtype selectivity (> 100 fold) for 5-HT 2A over 5-HT 2C receptors, however the question whether 29-31 act as agonists or antagonists has not been addressed.…”
Section: Wwwchemmedchemorgmentioning
confidence: 99%
“…N-alkylation or N,N-dialkylation proved detrimental to the potency of most phenylalkylamines. [172,174,175] An exception was found in a series of N-benzyl substituted phenylalkylamines; [176] affinity studies comparing 2C-B (11) with its N-benzylated analogues (29-31) revealed an approximate twofold increase in binding affinity for [ 125 I]DOI labeled 5-HT 2A receptors. Moreover compounds 29-31 showed increased subtype selectivity (> 100 fold) for 5-HT 2A over 5-HT 2C receptors, however the question whether 29-31 act as agonists or antagonists has not been addressed.…”
Section: Wwwchemmedchemorgmentioning
confidence: 99%
“…There is a significant literature correlating the binding affinity of DMT and related hallucinogens for the 5HT2A receptor and its subset of receptors with other hallucinogens and their subsequent behavioral effects (Glennon et al, 1978 ; Nichols, 2004 , 2016 ; Blough et al, 2014 ; Carbonaro and Gatch, 2016 ). However, DMT has been shown to interact with a variety of ionotropic and metabotropic receptors.…”
Section: Receptor Binding Of Dmt: 5-ht2a Taars and Sigma-1 Receptormentioning
confidence: 99%
“…DMT produces psychoactive effects through multiple neural mechanisms. DMT and related psychoactive tryptamines bind to numerous identified macromolecular sites comprising various serotonin, dopamine, and adrenergic receptors, [25][26][27][28][29] serotonin uptake transporters, [30][31][32][33] trace amine-associated receptors (TAARs), 34 monoamine oxidase enzymes, 35,36 and sigma-1 receptors. 37 Among the serotonin receptors, the 5-HT 2A receptor plays a key role in mediating the psychedelic effects of DMT, and experimental evidence points to the participation of 5-HT 1A , 5-HT 2B , 5-HT 2C , and 5-HT 7 receptors as well.…”
Section: Pharmacologymentioning
confidence: 99%